Editorial: Muscle oxygenation and vascular adaptations in sports performance and rehabilitation - Yáñez-Sepúlveda, Rodrigo (2024)
The investigation of muscle oxygenation through near-infrared spectroscopy (NIRS) has gained significant importance in the field of sports sciences. This is mainly due to its ability to non-invasively provide information on the energy metabolism of skeletal muscle, fatigue response, and health status of athletes. Additionally, during injury rehabilitation, strength-based metrics are often used. Still, they have not been based on metabolic and respiratory constraints that impact the athlete's energy expenditure. However, an approach relying on the measurement of muscle oxygen patterns has the potential to guide the rehabilitation of the skeletal muscle in physiotherapy and sports retraining and rehabilitation